Review: Revealing the genetic mechanisms of pre-harvest sprouting in hexaploid wheat (Triticum aestivum L.). (April 2019) - Vetch, Justin M.; Stougaard, Robert N.; Martin, John M.; Giroux, Michael J.
Highlights: Multiple genes have been associated with pre-harvest sprouting (PHS). Development of perfect markers underpinning PHS QTLs is necessary for efficient selection. TaMFT-3A allelic variation drastically impacts PHS. The ability to manipulate PHS will be enhanced by understanding how all genes that impact PHS together impact wheat dormancy. Abstract: Pre-harvest sprouting (PHS) of wheat ( Triticum aestivum L.) is an important phenomenon that results in weather dependent reductions in grain yield and quality across the globe. Due to the large annual losses, breeding PHS resistant varieties is of great importance. Many quantitative trait loci have been associated with PHS and a number of specific genes have been proven to impact PHS. TaPHS1, TaMKK3, Tamyb10, and TaVp1 have been shown to have a large impact on PHS susceptibility while many other genes such as TaSdr, TaQSd, and TaDOG1 have been shown to account for smaller, but significant, proportions of variation. These advances in understanding the genetics behind PHS are making molecular selection and loci stacking viable methods for affecting this quantitative trait. The current review article serves to provide a brief synthesis of recent advances regarding PHS, as well as provide unique insight into the genetic mechanisms governing PHS in bread wheat.